Understanding Measures of Association: A Primer With Examples From Rehabilitation Research. (August 2019) - Upadhye, Suneel; Alavinia, Mohammad; Kumbhare, Dinesh
Abstract : Abstract: Understanding measures of associations, how they are calculated, what they mean, and how to compare them is an important part of understanding clinical and health research. The relative risk and odds ratio are the two most common used measures of association in medical research. The appropriate use of these statistics to estimate the association between treatment or risk factor and outcome in research studies depends on the methodology and design of the study. The aim of this article was to cover basics of odds ratio and relative risk as the most important measures for the association between an exposure and an outcome. We use a clinical scenario as an example of their uses and demonstrate their calculation.